FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT RISIKO REKSADANA SAHAM - Nia Andriyani Ningsih; Yulia Efni; Edyanus Herman Halim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The purpose of this research is to inflation, ihsg, tingkat suku bunga take the influence risk mutual fund companies stock price in Bapepam-LK on 2009-2012. Sampling this researce are quantified by using purposive sampling method and the criterias spesifically based only on 36 companies.Hypothesises in this researce are tested by using analysis. From the result, inflation have significant influences risk mutual fund, ihsg, and tingkat suku bunga didn’t give either significant and positive influence to risk mual fund, R square in this research show on 0.325 which mean that the variation of risk mutual fund can be explained inflation, ihsg, tingkat suku bunga in amount of 32.5% while the remaining influence is determined by another variable outside this research.Keywords: risk mutual fund, inflation, ihsg , risk free rate